Territorial and environmental management in the indigenous lands of Paru de Leste river: a collective challenge in the northern Brazilian Amazon - van Velthem Linke, Iori Leonel; Apalaí, Cecília Awaeko; Guimarães Vieira, Ima Célia; Araújo Santos Jr., Roberto (Sustainability in Debate, 2020)
The National Policy for Environmental and Territorial Management of Indigenous Reserves ”“ (PNGATI in Portuguese) aims to promote quality of life in a sustainable way for indigenous peoples in their lands, respecting socio-cultural autonomy and their own forms of territoriality. This text shows and discusses its socio-political reach and mobilization involved in the implementation of PNGATI with the indigenous peoples of the Paru de Leste River, northern Amazon. Data were collected during the construction stages and execution of the Territorial and Environmental Management Plan through 2014 to 2018. The data suggest that despite some permanent implementation challenges, the management plan was built in order to respect the constitutional precepts of autonomy and collective well-being, empowering, within the limits of this public policy, the indigenous peoples of the region.